Color and Total Organic Carbon (TOC) Removal from Peat Water Using The Electrocoagulation Process: Central Composite Design for Optimization - Mirwan, Agus; Dessy, Sheilvina Milliviyanthi; Wicakso, Doni Rahmat; Suherman, Bella Febrianty Putri; Nurhalisa, Siti (BRIN Publishing (Penerbit BRIN), 2025)
The electrocoagulation process is simple and environmentally friendly. It removes pollutants in peat water such as color and total organic carbon (TOC). In this study, the electrocoagulation process was designed, optimized, and investigated using central composite design (CCD) type response surface methodology (RSM). The effects of current density and reaction time in the range of 6–14 mA/cm2 and 30–90 minutes on the efficiency of color and TOC treatment were evaluated. The best results for removing output efficiency were 10 mA/cm2 for 30 minutes (98.1% color) and 10 mA/cm2 for 30 minutes (91% TOC). By comparing actual and predicted data, the optimum condition in this process occurs when the current density is 6.140 mA/cm2 and the reaction time is 76.042 minutes. The experimental data can be well described using the central composite design